Kultura przestrzenią dialogu Kościoła ze światem po Vaticanum Secundum - KLAUZA, Karol (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The Second Vatican Council provides a complex and profound reflection on the contemporary culture. The Council’s most important document was the socalled Schema XII, which eventually took the form of the Pastoral Constitution on the Church in the Modern World Gaudium et Spes. The paper presents the history of the document and analyses its contents. On this basis, the relationship of the Church to culture in the past, as well as various aspects of Christian cultural identity, are discussed. Eventually, the author looks at the present culture and its possible, both positive and negative, developments. Translated by Patrycja Mikulska